2022
DOI: 10.3390/vaccines10122071
|View full text |Cite
|
Sign up to set email alerts
|

Monkeypox Disease (MPOX) Perceptions among Healthcare Workers versus General Population during the First Month of the WHO Alert: Cross-Sectional Survey in Saudi Arabia

Abstract: Background: Monkeypox disease (MPOX) recently re-emerged in May 2022, causing international outbreaks in multiple non-endemic countries. This study demonstrates a novel comparison between the knowledge and perceptions of Saudi healthcare workers (HCWs) and the general public regarding MPOX. Methods: An online survey, conducted from 27 May to 5 June 2022, assessing participants’ MPOX and monkeypox virus (MPV) knowledge in terms of transmission, vaccination, isolation precautions, and their attitudes toward seek… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…For example, MPOX vaccination can have an important role in the preventive efforts for high-risk groups, including HCWs [ 19 ]. Additionally, satisfactory knowledge and positive attitude towards MPOX vaccination can affect HCWs’ recommendation of the vaccine for other high-risk groups (e.g., men who have sex with men (MSM)) [ 28 , 40 ]. Specifically, and in the context of MPOX vaccination intention among the general public in the U.S., Winters et al reported that the most trusted sources of information regarding the outbreak were HCWs [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, MPOX vaccination can have an important role in the preventive efforts for high-risk groups, including HCWs [ 19 ]. Additionally, satisfactory knowledge and positive attitude towards MPOX vaccination can affect HCWs’ recommendation of the vaccine for other high-risk groups (e.g., men who have sex with men (MSM)) [ 28 , 40 ]. Specifically, and in the context of MPOX vaccination intention among the general public in the U.S., Winters et al reported that the most trusted sources of information regarding the outbreak were HCWs [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, prevention and treatment of infectious disease is a complicated process, as it often requires going beyond providing information, implementing preventive measures, which is dictated by the knowledge of the disease, attitudes toward prevention, and intentions to adopt recommended practices [ 21 ]. According to previous and recent studies involving health professionals, addressing gaps in MPOX knowledge can be considered an integral step to change attitudes and behavior [ 23 , 24 , 25 , 26 , 27 , 28 ]. When attitudes are grounded with high knowledge, they are associated with more enduring and better predictors of behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…raising awareness, strengthening information campaigns) and surveillance are essential priorities for high‐risk population groups in non‐endemic countries. These approaches prevent viral transmission (Temsah et al, 2022; Zardi & Chello, 2022). Despite limited evidence‐based preventive interventions, government and healthcare personnel can use COVID‐19 pandemic knowledge (Lulli et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted in Saudi Arabia comparing information‐seeking about monkeypox and vaccination knowledge between the general public and healthcare workers (HCWs) revealed that HCWs (74.2%) demonstrated a higher interest in information‐seeking than the general public (61.35%; Temsah et al, 2022). Interestingly, HCWs reported poor vaccination knowledge, while female HCWs in secondary and tertiary health centres with high monkeypox awareness showed significantly higher knowledge levels (Temsah et al, 2022). These findings indicate that HCWs may not recommend vaccination as one of the ways to prevent monkeypox.…”
Section: Introductionmentioning
confidence: 99%
“…When a study was carried out with the aim of understanding how many general practitioners have sound knowledge regarding Mpox, it was revealed that only 27% (Italy), and 18.6% (Saudi Arabia). Another study carried out in Saudi Arabia revealed that 48% of the general population had sufficient knowledge about Mpox [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%